2008
DOI: 10.1242/dmm.001248
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish myelination: a transparent model for remyelination?

Abstract: There is currently an unmet need for a therapy that promotes the regenerative process of remyelination in central nervous system diseases, notably multiple sclerosis (MS). A high-throughput model is, therefore, required to screen potential therapeutic drugs and to refine genomic and proteomic data from MS lesions. Here, we review the value of the zebrafish (Danio rerio) larva as a model of the developmental process of myelination, describing the powerful applications of zebrafish for genetic manipulation and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 104 publications
(111 reference statements)
0
48
0
2
Order By: Relevance
“…Canonical Wnt signaling is necessary to drive myelination in vivo A key role for the Wnt/␤-catenin pathway in PNS and CNS myelination was demonstrated by loss-of-function strategies in zebrafish embryos, which has become a powerful model to assess myelination in living embryos (Lyons et al, 2005;Kirby et al, 2006;Buckley et al, 2008). That is, most of the critical molecular machinery of myelination is conserved between zebrafish and mammals (Monk and Talbot, 2009).…”
Section: Components Of the Canonical Wnt Signaling Pathway Drive Myelmentioning
confidence: 99%
“…Canonical Wnt signaling is necessary to drive myelination in vivo A key role for the Wnt/␤-catenin pathway in PNS and CNS myelination was demonstrated by loss-of-function strategies in zebrafish embryos, which has become a powerful model to assess myelination in living embryos (Lyons et al, 2005;Kirby et al, 2006;Buckley et al, 2008). That is, most of the critical molecular machinery of myelination is conserved between zebrafish and mammals (Monk and Talbot, 2009).…”
Section: Components Of the Canonical Wnt Signaling Pathway Drive Myelmentioning
confidence: 99%
“…To combat MS effectively, especially in patients who are in later stages of the disease, there is an urgent requirement for therapies that promote the regeneration of myelin sheaths (remyelination) (Dubois-Dalcq et al, 2005Franklin and ffrench-Constant, 2008;Irvine and Blakemore, 2008). Zebrafish and mammalian oligodendrocytes and myelin are homologous and zebrafish are increasingly being used to investigate myelination through the use of fluorescence transgenesis and genetic manipulation (reviewed by Buckley et al 2008). It has therefore been suggested that a zebrafish model of oligodendrocyte development and myelination could provide an efficient, in vivo method of screening for potential remyelination therapies (Buckley et al, 2008;DuboisDalcq et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish and mammalian oligodendrocytes and myelin are homologous and zebrafish are increasingly being used to investigate myelination through the use of fluorescence transgenesis and genetic manipulation (reviewed by Buckley et al 2008). It has therefore been suggested that a zebrafish model of oligodendrocyte development and myelination could provide an efficient, in vivo method of screening for potential remyelination therapies (Buckley et al, 2008;DuboisDalcq et al, 2008). A key advantage of using the zebrafish larva as a screening model is its rapid development and the consequent potential for designing highthroughput screens.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include assessment of morphological mutant phenotypes, protein or nucleic acid expression patterns, and developmental stages. [1][2][3] Part of the challenge in obtaining consistent, high-quality images of the zebrafish arises from efforts in attaining static two-dimensional images of a dynamic three-dimensional sample. Additional difficulty comes from the shift of a largely spherical early embryo (0-24 hour postfertilization [hpf ]) to the cylindrical shape of the larvae and adult fish.…”
mentioning
confidence: 99%
“…The issues of working with this unique shape have inspired many methods that attempt to remedy these problems and deliver consistent, high-quality image capture. [1][2][3][4] However, all of these approaches still require substantial training to achieve proficiency, are laborious, and thus are often not practical for high-throughput screening or other applications. Quality imaging can be the most critical bottleneck in using the fish for many scientific areas.…”
mentioning
confidence: 99%